Acolhimento no estágio: entre modelos e possibilidades de formação docente - Araújo, Simone Reis Palermo Machado de [UNESP] (2014)
This research focuses on how teachers understand their role when they have pre-service teachers in their classrooms. This research also aims to understand how they assess such such experience, which is part of their formation as teachers. The study is qualitative-based and has elements of ethnographic research. The field research was developed in elementary school by systematical observation of two pre-service teachers of the Pedagogy course of a public university of the State of São Paulo and the teachers with whom they paired up with and received mediations from over the practical training period. This practical training is developed under a project which valorize the intergenerational partnerships for teacher education. The collected data shows the observation of the pairs formed by teachers/preservice teachers. The data collection was complemented by two semi-structured interviews; the first of which done before the starting of the practical training process and the other done at the end of the observation period. During the development of the research a third pair emerged. Information regarding this third pair was collected by interview and by the observation of a meeting between the teacher and the pre-service teacher. The data was analyzed with principles of content analysis and explored by different categories. The results show that teachers chose to welcome the pre-service teachers (not just have them in their classrooms), taking their formative needs into consideration and including them in their daily routine activities. The teachers welcomed the pre-service teachers in different ways: the first one we call modeling, in wich the teacher acts as master; and the second is a formative welcome, which proved itself to be potentially self-formative for the teachers. The teachers considered that they performed a formative role on the pre-service teachers' practical training, identifying that there is a place for teachers in the...